Asymmetric Aminocatalytic Michael Addition of Cyclopropane-Containing Aldehydes to Nitroalkenes - Reitel, Kärt; Lippur, Kristin; Järving, Ivar; Kudrjašova, Marina; Lopp, Margus; Kanger, Tõnis (Synthesis, 2013)
An asymmetric aminocatalytic approach to alkylidenecyclopropane derivatives via Michael addition of aldehydes to nitroalkene derivatives was developed.
Keywords: asymmetric catalysis; Michael addition; amines; organocatalysis; alkylidenecyclopropane